Native LDL promotes differentiation of human monocytes to macrophages with an inflammatory phenotype - Al-Sharea, Annas; Lee, Man Kit Sam; Moore, Xiao-Lei; Fang, Lu; Sviridov, Dmitri; Chin-Dusting, Jaye; Andrews, Karen L.; Murphy, Andrew J. (Thrombosis and Haemostasis, 2016)
Recruitment of monocytes in atherosclerosis is dependent upon increased levels of plasma lipoproteins which accumulate in the blood vessel wall. The extracellular milieu can influence the phenotype of monocyte subsets (classical: CD14++CD16-, intermediate: CD14+CD16+ and non-classical: CD14dimCD16++) and macrophages (M1 or M2) and consequently the initiation, progression and/or regression of atherosclerosis. However, it is not known what effect lipoproteins, in particular native low-density lipoproteins (nLDL), have on the polarisation of monocyte-derived macrophages. Monocytes were differentiated into macrophages in the presence of nLDL. nLDL increased gene expression of the inflammatory cytokines TNFα and IL-6 in macrophages polarised towards the M1 phenotype while decreasing the M2 surface markers, CD206 and CD200R and the anti-inflammatory cytokines TGFβ and IL-10. Compared to the classical and intermediate subsets, the non-classical subset-derived macrophages had a reduced ability to respond to M1 stimuli (LPS and IFNγ). nLDL enhanced the TNFα and IL-6 gene expression in macrophages from all monocyte subsets, indicating an inflammatory effect of nLDL. Further, the classical and intermediate subsets both responded to M2 stimuli (IL-4) with upregulation of TGFβ and SR-B1 mRNA; an effect, which was reduced by nLDL. In contrast, the non-classical subset failed to respond to IL-4 or nLDL, suggesting it may be unable to polarise into M2 macrophages. Our data suggests that monocyte interaction with nLDL significantly affects macrophage polarisation and that this interaction appears to be subset dependent.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Monocyte subsets; macrophages; native LDL; polarisation